1982
DOI: 10.1111/j.1600-0587.1982.tb01045.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a lake fertilization on the stability and material utilization of a limnetic ecosystem

Abstract: The interaction between the phytoplankton, zooplankton and fish populations and certain abiotic environmental factors, was investigated in an oligotrophic Norwegian lake during a 5‐yr period (1974–1978). The effects of adding artificial fertilizer in 1975 and 1976 were also studied. When cladoceran dominated, the zooplankton community was able to maintain a more or less constant phytoplankton biomass and a rather low phytoplankton production even when nutrient levels were raised. In years when rotifers were do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 21 publications
0
33
1
Order By: Relevance
“…Nevertheless, consistent with previous study indicating a competitive superiority of mixotrophic nanoflagellates (Palsson & Graneli, 2004), we observed that the abundance of C. parva was inversely related to TDP concentration. This result differed from studies in Norwegian and Swedish lakes where C. parva populations increased after fertilization (Reinertsen & Langeland, 1982;Holmgren, 1984). However, in incubation experiments manipulating zooplankton biomass, it was observed that the abundance of C. parva decreased with increased zooplankton biomass despite increased concentrations of P due to nutrient recycling (Balseiro et al, 1997).…”
Section: Discussioncontrasting
confidence: 68%
“…Nevertheless, consistent with previous study indicating a competitive superiority of mixotrophic nanoflagellates (Palsson & Graneli, 2004), we observed that the abundance of C. parva was inversely related to TDP concentration. This result differed from studies in Norwegian and Swedish lakes where C. parva populations increased after fertilization (Reinertsen & Langeland, 1982;Holmgren, 1984). However, in incubation experiments manipulating zooplankton biomass, it was observed that the abundance of C. parva decreased with increased zooplankton biomass despite increased concentrations of P due to nutrient recycling (Balseiro et al, 1997).…”
Section: Discussioncontrasting
confidence: 68%
“…The low value of both orthophosphate and nitrate recorded in the summers 1977 and 1978 imply that the residual levels of both nutrients were low and that cyclic processes in the system were responsible for the supply of nutrients for growth. In such circumstances nitrogen can be considered the limiting element, since this element had the slowest turnover rate reeorded in all investigated years (Reinertsen and Langeland 1982). Other investigations confirm that phosphorus can be reeycled more rapidly than nitrogen in the euphotie zone (Goldman et al 1979).…”
Section: Discussionmentioning
confidence: 85%
“…2). The thermoeline developed within 10-11 d in 1974, 1976 and 1978, and within 24-25 d in 1975 and 1977. During the first part of the summer the thermoeline was usually recorded between 4-5 m depth, but moved during the summer to an even deeper level (Langeland and Reinertsen 1982).…”
Section: Water Temperature and Light Conditionsmentioning
confidence: 99%
“…Wetzel, 1983), and it also has consequences for the quantitative role of heterotrophic bacteria (Currie, 1990;White et aI., 1991;Simon et aI., 1992). Recently, focus has been put on the importance of the food web structure for stability and material utilization in lakes (e.g., Andersson et ai., 1978;Reinertsen and Langeland, 1982;Benndorf, 1987;Andersen, 1997). A key factor in this respect is the control of planktonic algae by herbivorous grazers.…”
Section: Heterotrophic Bacteria and Carbon Cycling In Lakesmentioning
confidence: 99%